A New Protocol for Catalytic Reduction of Alkyl Chlorides Using an Iridium/Bis(benzimidazol-2′-yl)pyridine Catalyst and Triethylsilane - Fukuyama, Takahide; Hamada, Yuki; Ryu, Ilhyong (Synthesis, 2021)
The reduction of alkyl chlorides using triethylsilane is investigated. Primary, secondary, tertiary, and benzylic C–Cl bonds are effectively converted into C–H bonds using an [IrCl(cod)]2/2,6-bis(benzimidazol-2′-yl)pyridine catalyst system. This catalyst system is quite simple since the tridentate N-ligand can be easily prepared in one step from commercially available reagents.
Keywords: reduction; alkyl chlorides; iridium catalyst; nitrogen ligand; triethylsilane